Place de la Bastille. The French farmers demonstrate against the agricultural policy of the E.E.C. and of the French government. Series of 4 photos - Langkau-Alex, Ursula,
Place de la Bastille. The French farmers demonstrate against the agricultural policy of the E.E.C. and of the French government. Series of 4 photos.